Crystal Structure of Nonstructural Protein 10 from the Severe Acute Respiratory Syndrome Coronavirus Reveals a Novel Fold with Two Zinc-Binding Motifs - Joseph, Jeremiah S.; Saikatendu, Kumar Singh; Subramanian, Vanitha; Neuman, Benjamin W.; Brooun, Alexei; Griffith, Mark; Moy, Kin; Yadav, Maneesh K.; Velasquez, Jeffrey; Buchmeier, Michael J.; Stevens, Raymond C.; Kuhn, Peter (Journal of Virology, 2006)
Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI